Pengaruh Konsentrasi Natrium Metabisulfit Terhadap WarThe Effect of Sodium Metabisulfite Concentration on the Color of Champignon Mushrooms in Pouch Packaging on the Color of Champignon Mushrooms in Pouch Packaginga Jamur Champignon Pada Kemasan Pouch - Yunita Khilyatun Nisak; Affandi Trilistyadi (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Champignon mushrooms (Agaricus bisporus) are highly perishable due to their highwater content and rapid respiration rate, which accelerates browning reactions. One method to maintain their quality is by applying sodium metabisulfite (Na₂S₂O₅). This study aimed to investigate the effect of different concentrations of sodium metabisulfite on the color of champignon mushrooms. The research was conducted using a Completely Randomized Design (CRD) with one factor and four treatment levels: 0.1%, 0.15%, 0.2%, and 0.25%. Data were analyzed using one-way ANOVA in Minitab with a 95% confidence interval (α = 0.05). The results showed that sodium metabisulfite had a significant effect on brightness (L*) and yellowness (b*) values. The best treatment was observed at the 0.25% concentration, which produced the brightest mushroom color with a brightness value (L*) of 98.54, a redness value (a*) of 1.2, and a yellowness value (b*) of 6.74.